Association of geriatric nutritional risk index with total testosterone in elderly adults in the US: evidence from NHANES 2011-2016 - Li, Tanjian; Jiang, Na; Liang, Xin; Li, Xinya; Li, Yaqin; Huang, Yuting; Wang, Yu (Frontiers in Endocrinology, 2024)
Background and objectivesThere is growing evidence that deficiencies in specific nutrients can impact testosterone levels in older men. However, research examining the predictive value of overall nutritional status on testosterone levels remains limited. The Geriatric Nutritional Risk Index (GNRI) is an effective tool for assessing the nutritional status of the elderly. Therefore, this study aimed to investigate the potential correlation between the GNRI and serum total testosterone (TT).MethodsA representative sample of U.S. males aged 60 years and older who participated in the National Health and Nutrition Examination Survey (NHANES) cycles from 2011 to 2016 was utilized for this cross-sectional study. The research included a total of 829 older adults. Tandem mass spectrometry and liquid chromatography were employed to quantify TT. To examine the association between GNRI and TT, restricted cubic splines (RCS) and weighted multivariate regression analyses were conducted. Subgroup analysis was performed to identify the variables influencing the positive association between GNRI and TT. Additionally, a sensitivity analysis was carried out to compare the weighted and unweighted data.ResultsAfter adjusting for all other factors, a positive association was found between GNRI and TT. The beta coefficient was 5.59, with a 95% confidence interval of 2.16 to 9.01, and a p-value of 0.003. Compared to the lowest quartile of GNRI (Q1), the second quartile (Q2), third quartile (Q3), and fourth quartile (Q4) significantly increased the level of TT. The beta coefficients for Q2, Q3, and Q4 were 70.15 (p = 0.022), 104.40 (p < 0.001), and 84.83 (p < 0.001), respectively. In subgroup analyses, statistically significant associations were observed among participants who did not have diabetes, had hypertension, and had a BMI of 24.9 or less. According to the sensitivity analysis, unweighted data also found GNRI to be associated with TT (beta = 3.09, P = 0.031).ConclusionA positive correlation was identified between the GNRI and TT in the elderly male population of the United States. Further prospective studies with larger sample sizes are needed to confirm the causal relationship between GNRI and TT.